Determining factors of childhood obesity: Its impacts and influences (Research, Society and Development, 2025)
Introduction: Childhood obesity is growing worldwide and is already considered one of the greatest public health concerns. This situation goes beyond childhood overweight, as it can impair healthy growth, increase the risk of diseases in adulthood, and generate emotional and social impacts that affect children's daily lives. Objective: To investigate the main factors contributing to childhood obesity and understand its effects on physical, psychological, and social health.  Final thoughts: childhood obesity isn't caused by a single factor, but is the result of various habits and situations that are part of a child's life. To avoid this problem, we need to join forces in different areas, create policies that encourage healthier eating, ensure safe places to play and exercise, control advertising of ultra-processed products, and strengthen nutrition education in schools. In this scenario, nutritionists play a very important role in helping families and communities make better choices, thus contributing to children growing up healthier and with a better quality of life.